PENGARUH LATIHAN DRY LAND TERHADAP PENINGKATAN KECEPATAN RENANG 50 METER GAYA KUPU-KUPU PADA ATLET RENANG LANJUTAN SEARIA AQUATIC PADANG - M. Fandy Yudha Fayzatama; Naluri Denay; Pringgo Mardesia; Yogi Arnaldo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is that advanced athletes at the Searia Aquatic Club still have relatively low achievements in butterfly swimming events, especially in the 50-meter butterfly sprint. This can be seen from the inconsistent achievements of athletes in various swimming events or championships they participate in. Advanced athletes at the Searia Aquatic Club still have difficulty competing and achieving maximum results regularly. This study aims to determine the effect of Dry Land Swimming Training on Increasing the Speed ​​of 50 Meter Butterfly Swimming in SeaRia Aquatic Swimming Athletes. This study uses a quasi-experimental method. The research sample consisted of 10 people with a purposive sampling technique. The instrument used was a 50-meter butterfly swimming test. The results of the study showed that in the hypothesis test with T count of 16.714 and T table of 2.262 in accordance with the concept of decision making 16.714 > 2.262, so it can be concluded that dry land training has a significant effect.